Analysis of User Benefits of Sidepe Demographic System with the EUEC Method - Andi Arfian; Alvi Yana; Juarmi Siregar (JTKSI (Jurnal Teknologi Komputer dan Sistem Informasi), 2023)
The current research is mainly aimed at validating the End User Computing Satisfaction (EUCS) model in the sidepe population system in Cikedokan Village, Bekasi Regency. In the EUCS model, the Logit model is applied to seven items. This research data is using a questionnaire method. This research method applies the End-User Computing Satisfaction (EUCS) model by means of quantitative and dissemination of questionnaires to obtain information from the research object. The population in this research is Cikedokan villagers. From this population, 80 respondents were selected and the dissemination of questionnaires was carried out through questionnaires by means of simple random sampling. After that, the collected data was processed with PLS-SEM. As a result, there are 5 paths tested, H1 to H4 are rejected for four variables and H5 is accepted for one variable. There are four variables that do not have a significant effect on user satisfaction (User satisfaction). The Sidepe system in Cikedoka village is less than optimal in its utilization